The storm-god in the ancient Near East - Green, Alberto Ravinell Whitney (Biblical and Judaic studies, 2003)
"The Storm-god was a deity common to every culture in the ancient Near East. In this comprehensive study of the literature, iconography (seals, monuments), and myths related to the Storm-god in its various guises, Alberto Green attempts a new synthesis of the available data. He finds that the Storm-god was the force primarily responsible for three areas of human concern: (1) religious power, because he was the ever-dominant environmental force upon which peoples depended for their lives; (2) centralized political power; and (3) continuously evolving sociocultural processes, which typically were projected through the Storm-god's attendants. Green traces these motifs through the Mesopotamian, Anatolian, Syrian, and Levantine regions; he argues that, in the end, Yahweh of the Bible can be identified as a storm-god, though certain unique characteristics came to be associated with him: he was the creator of all that is created and the self-existing god who needs no other."--Jacket.